Clinical characteristics and survival outcomes of newly diagnosed multiple myeloma patients presenting with extramedullary disease: A retrospective study. (April 2022) - Gao, Shuang; Li, Qihui; Dong, Fei; Yang, Ping; Chen, Yingtong; Wang, Jing; Wang, Yanfang; Jing, Hongmei
Abstract: The aim of study was to assess the clinical characteristics, survival outcomes of newly diagnosed multiple myeloma (NDMM) patients with extramedullary disease (EMD). We retrospectively reviewed and compared the clinical features and outcomes in 226 MM patients with or without EMD at their diagnosis. EMD patients were subsequently divided into bone-related (EMD-B) and soft-tissue related (EMD-S). EMD group was composed of 29.2% of the patients and the incidence of EMD-B and EMD-S was 19.0% and 10.2% respectively. EMD at diagnosis had greater prevalence of IGH/FGFR3 translocation (7.6% vs 2.5%, p = 0.028) and a worse objective response rate (75% vs 88.9%, p = 0.015). The overall survival (OS) of EMD and non-EMD patients were 44 months and 82 months respectively (p < 0.001)，and the progression-free survival were 24 months and 36 months respectively (p = 0.014). Multivariate analysis showed EMD at diagnosis, hypercalcemia, and elevated LDH were independent prognostic factors. Prevalence of anemia, elevated LDH, 1q21 + were greater in EMD-S and OS of EMD-S was significantly poorer (51months vs 26 months, p = 0.0067) compared with EMD-B. Autologous hematopoietic stem cell transplantation (auto-HSCT) could partly overcome the adverse effect of EMD. Highlights: EMD and EMD-S at diagnosis predict poor prognosis in MM. EMD and EMD-S had high incidence of IGH/FGFR3 rearrangement and 1q21 + respectively. Auto-HSCT prolongs both EMD and EMD-S patients' PFS.